2007
DOI: 10.1007/s11746-007-1036-6
|View full text |Cite
|
Sign up to set email alerts
|

Hexanal Synthesis in Isolated Soy Proteins

Abstract: Sodium erythrobate (2.3 mM) and dithiothreitol (6.5 mM) caused headspace hexanal from aqueous slurries of commercial isolated soy proteins (ISP) to increase by as much as 13-fold compared with headspace hexanal in the controls. When linoleic acid was also added, headspace hexanal levels from commercial and laboratory-prepared ISP were further increased by as much as 18-and 136-fold, respectively, compared with the levels in the controls. When 13 Clabeled linoleic acid was added to aqueous mixtures of laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…When the same level of DTT was added together with linoleic acid (0.16 mM), no further increase in hexanal synthesis was found in all tested samples except for ISO‐I 974C, for which the reason is unclear. Variations in hexanal synthesis among the ISP samples in response to the treatments with DTT or/and linoleic acid were observed from both current study and previous investigation (Boatright and Lu 2007). The reported protein ( N × 5.71) and lipid contents in lab ISP were 77.9% to 84.5% (Boatright and others 1998) and 4.50% to 4.87% (Boatright and Lu 2007), respectively.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…When the same level of DTT was added together with linoleic acid (0.16 mM), no further increase in hexanal synthesis was found in all tested samples except for ISO‐I 974C, for which the reason is unclear. Variations in hexanal synthesis among the ISP samples in response to the treatments with DTT or/and linoleic acid were observed from both current study and previous investigation (Boatright and Lu 2007). The reported protein ( N × 5.71) and lipid contents in lab ISP were 77.9% to 84.5% (Boatright and others 1998) and 4.50% to 4.87% (Boatright and Lu 2007), respectively.…”
Section: Resultssupporting
confidence: 81%
“…Variations in hexanal synthesis among the ISP samples in response to the treatments with DTT or/and linoleic acid were observed from both current study and previous investigation (Boatright and Lu 2007). The reported protein ( N × 5.71) and lipid contents in lab ISP were 77.9% to 84.5% (Boatright and others 1998) and 4.50% to 4.87% (Boatright and Lu 2007), respectively. In addition, no differences in the iron contents from the ISPs tested in the current study were observed (data not shown).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Typically, commercial ISP samples contain about 4% total lipids (mostly phospholipids) that are carried through the protein purification process bound to the protein (Boatright and Hettarachchy 1995; Boatright and Crum 1997; Boatright and Lu 2007). The reported lipid contents of laboratory prepared ISP samples are slightly lower at 3.5% to 4.0%.…”
Section: Resultsmentioning
confidence: 99%